Employee and Customer Injury During Violent Crimes in Retail and Service Businesses - Peek-Asa, Corinne (© American Journal of Public Health 2006, 2006)
Objectives. We sought to compare the frequency and risk factors for employees and customers injured during crimes in retail (convenience, grocery, and liquor stores) and service businesses (bars, restaurants, motels). Methods. A total of 827 retail and service businesses in Los Angeles were randomly selected. Police crime reports (n=2029) from violent crimes that occurred in these businesses from January 1996 through June 2001 were individually reviewed to determine whether a customer or an employee was injured and to collect study variables. Results. A customer injury was 31% more likely (95% confidence interval [CI]=1.11, 1.51) than an employee injury during a violent crime. Customer injury was more frequent than employee injury during violent crimes in bars, restaurants, convenience stores, and motels but less likely in grocery or liquor stores. Injury risk was increased for both employees and customers when resisting the perpetrator and when the perpetrator was suspected of using alcohol. Customers had an increased risk for injury during crimes that occurred outside (relative risk [RR]=2.01; 95% CI=1.57, 2.58) and at night (RR=1.79; 95% CI=1.40, 2.29). Conclusions. Security programs should be designed to protect customers as well as employees.